Development of a process for the removal of natural radionuclides and other stable pollutants from acid phosphogypsum stacks leachates. Issue 1 (February 2023) - Pérez-Moreno, S.M.; Romero, C.; Guerrero, J.L.; Gázquez, M.J.; Bolívar, J.P.
Abstract: In Huelva, there are phosphogypsum (PG) deposits built over the salt marshes of the Tinto River, less than 1 km from the city, which accumulate about 100 million tons covering an area of 1000 ha. These deposits release natural radionuclides and other pollutants into their surrounding environment through highly acidic leachates (pH < 2) in the form of surface runoff and groundwater fluxes, which emerge as lateral leachates. The concentration of natural radionuclides in these leachates, especially U-isotopes and 210 Po, exceed by 4 orders of magnitude the activity concentrations found in unpolluted sea waters. Furthermore, the concentration of heavy metals (As, Cr, Cd, Cu, Ni, Zn, etc.) and anions (F -, PO4 3- and SO4 2- ) are also significantly higher. In this work, the neutralization process of these acidic leachates was studied by using different alkaline chemical reagents (Ca(OH)2, CaCO3, NaOH, Na2 CO3, Mg(OH)2, MgCO3 ), on a laboratory scale. In addition, speciation of the components was modelled with the aim of designing an optimum alkaline treatment for phosphate recovery. The treatment of phosphogypsum leachates (PGL) by neutralization using Ca(OH)2 is a considerable option for the removal of their contaminants by precipitation, obtaining a clean liquid that, after filtration, could be discharged into the environment with an extremely low potential risk, since a high removal efficiency was obtained. The speciation simulation carried out suggests that UO2 HPO4 is the main uranium species present in the PGL, and, for polonium, it seems to be Po 2+, which is relevant for their removal process. Graphical Abstract: ga1 Highlights: The neutralization process of the phosphogypsum leachates has been studied. A completely removal of radionuclides and other contaminants has been achieved. Speciation of the components has been modelled during the treatment. The treated leachate could be discharged without any environmental impact.